Students’ Perceptions of Dubbing Muted Animation in English Speaking Classrooms: A Case Study at Greenfield Language College (GRACE) - Ariani; Syarifuddin Dollah; Andi Anto Patak; Fitriani (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This paper aims to explore students' perceptions of using the dubbing muted animation movie clip technique in English speaking classrooms at Greenfield Language College. We employed a case study as our research design. By using convenient sampling, we recruited 5 participants to participate in our study. The results show that students at Greenfield Language College overwhelmingly perceive the dubbing muted animation movie clip technique in English speaking classrooms as a highly positive pedagogical approach, as evidenced by recurring themes of enjoyment and interest, increased speaking confidence, and a proactive engagement with challenges and difficulties. This study contributes to a more nuanced understanding of effective multimedia integration in language pedagogy and offers valuable insights for curriculum developers and educators.